2000
DOI: 10.1063/1.372515
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-optical behavior in Co/Pt ultrathin film multilayers

Abstract: Magneto-optical Kerr effect measurements performed on ͑0.3 nm Co/x Pt) 15 multilayers with xϭ0.3-2.0 nm showed all samples to exhibit strong perpendicular magnetic anisotropy. Recent work has shown that for compositions near ͑0.3 nm Co/1.2 nm Pt͒ 15 , both polar Kerr rotation and ellipticity exhibit bimodal reversals in which the major hysteresis loops have two distinct field-dependent steps due to the contributions of two magnetic phases. To better understand this bimodal magnetization phenomenon, Kerr rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Pt cap layers on the top of the Co-layer deposited on fcc(111)-Pt are needed to prevent oxidation of the surface [7]. We found that only multilayer systems with Pt cap layers exhibit perpendicular magnetization to the surface.…”
Section: Resultsmentioning
confidence: 87%
“…Pt cap layers on the top of the Co-layer deposited on fcc(111)-Pt are needed to prevent oxidation of the surface [7]. We found that only multilayer systems with Pt cap layers exhibit perpendicular magnetization to the surface.…”
Section: Resultsmentioning
confidence: 87%
“…9,31 In Co/Pt multilayers the authors found a bimodal hysteresis cycle which was due ͑as evidenced by Kerr microscopy͒ to the existence of two distinct magnetic phases on the surface. Both phases had different magnetic responses to applied fields.…”
Section: Discussionmentioning
confidence: 97%
“…The reason for this surely arises from the large sensitivity of the magnetic anisotropy to structural, morphological, and chemical details at the interfaces, which is at the origin of a variety of experimental results due to a lack of complete and accurate control of the fabrication parameters. A few examples include growth-induced perpendicular anisotropy in thin alloy films grown at 200-400°C, 8 the existence of two distinct magnetic phases in multilayers prepared at 200°C, 9 and the suppression of the perpendicular anisotropy by trace amounts of contaminants. 10 In this paper we present results for ultrathin Co films grown on Pt͑111͒, investigated with x-ray diffraction both in its standard form and also in resonant scattering, to sense the magnetism of the Pt atoms at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, in experiments Pt cap layers are deposited on top of Co in order to prevent the oxidation of the surface. [44] By performing a separate, magnetic anisotropy calculation, [43] we have found that Co|Pt(111) exhibits perpendicular magnetization only in the presence of Pt cap layers. Therefore, for the polar Kerr spectra of the Co|Pt 5 |Pt(111) system shown in Fig.…”
Section: Polar Kerr Effect For Normal Incidencementioning
confidence: 97%